Odpowiedź :
Odpowiedź:
[tex]2x + 17 = 26 - x \\ 2x + x = 26 - 17 \\ 3x = 9 \: \: \: \: \: | \div 3 \\ x = 3[/tex]
[tex]11 - x = 3x + 8 \\ - x - 3x = 8 - 11 \\ - 4x = - 3 \: \: \: \: | \div ( - 4) \\ x = \frac{3}{4} [/tex]
[tex] - 7(x - 2) + 4 = - 3 \\ - 7x + 14 + 4 = - 3 \\ - 7x = - 21 \: \: \: \: \: | \div ( - 7) \\ x = 3[/tex]
Odpowiedź:
a.
2x + 17 = 26 - x
2x + x = 26 - 17
3x = 9 /:3
x = 3
b.
11 - x = 3x + 8
-x - 3x = 8 - 11
-4x = -3 /:(-4)
x = 3/4
c.
-7 (x-2) + 4 = -3
-7x + 14 + 4 = -3
-7x = -3 - 18 /:(-7)
x = 21/7 = 3
Szczegółowe wyjaśnienie: